Lens barrel structure and optical imaging lens - GUO CHENGLI; DAI FUJIAN; LI YUANZHENG; ZHAO LIEFENG (2023)
The utility model provides a lens cone structure and an optical imaging lens, the lens cone structure comprises two half lens cones, the half lens cones are provided with connecting surfaces, the connecting surfaces are provided with plug connectors, plug grooves, first groove structures and second groove structures, the first groove structures extend from the outer wall surfaces of the half lens cones to the plug connectors, and the second groove structures extend from the outer wall surfaces of the half lens cones to the plug connectors. The first groove structure extends from the outer wall surface of the half lens cone to the inserting groove, the second groove structure extends from the outer wall surface of the half lens cone to the inserting groove, the connecting surfaces of the two half lens cones are correspondingly connected, the inserting piece on one half lens cone extends into the inserting groove in the other half lens cone, and the first groove structure and the second groove structure are cor